2022
DOI: 10.1111/jpm.12869
|View full text |Cite
|
Sign up to set email alerts
|

Experiences of familial stigma among individuals living with mental illnesses: A meta‐synthesis of qualitative literature from high‐income countries

Abstract: What is known on the subject?:• Mental illness stigma has been long acknowledged as a social problem that continues to persist and contribute to social exclusion of affected persons globally.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 98 publications
1
6
0
Order By: Relevance
“…In this study, gender (male) and age were also associated with increased perception of stigma agreement as well as a positive reaction towards mental illness. This finding is in line with previous studies (Adu et al, 2022; Al Omari et al, 2021; Rayan & Jaradat, 2016). There is accumulated research evidence that many younger age groups have a positive attitude towards people with mental illness (DuPont‐Reyes et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…In this study, gender (male) and age were also associated with increased perception of stigma agreement as well as a positive reaction towards mental illness. This finding is in line with previous studies (Adu et al, 2022; Al Omari et al, 2021; Rayan & Jaradat, 2016). There is accumulated research evidence that many younger age groups have a positive attitude towards people with mental illness (DuPont‐Reyes et al, 2020).…”
Section: Discussionsupporting
confidence: 93%
“…An older brother always scolds his ill brother for not going to work, which is seen as lazy and irresponsible 18 . Family abusive behaviors towards PLS are the most visible familial stigma of mental illness, but are rarely reported in the literature, especially in low- and middle-income countries 14 . Family abusive behaviors towards PLS are destructive and hidden.…”
Section: Discussionmentioning
confidence: 99%
“…A scoping review found that the “perpetrators” of microaggressions (brief and commonplace daily verbal, behavioral, or environmental indignities that communicate hostile, derogatory, or insults) toward people with mental illness were predominantly family members, rather than strangers or acquaintances 16 . Researchers have described how PLS experienced abusive behavior from their family caregivers in some qualitative studies 14 , 17 , 18 . Those studies explored the nature, types, and experiences of abusive behavior by family caregivers toward PLS, but rarely reported its prevalence and studied its consequences.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations